ヒガシ オングルトウ ヨリ エタ ケイソウ ヨホウ 2 - 福島, 博; フクシマ, ヒロシ; 綿貫, 知彦; ワタヌキ, トモヒコ; 小林, 艶子; コバヤシ, ツヤコ; FUKUSHIMA, Hiroshi; WATANUKI, Tomohiko; KO-BAYASHI, Tsuyako (国立極地研究所, 1975)
P(論文) In this paper are reported 31 taxa of diatom. Among these taxa, Achnanthes lanceolata, Asterionella gracillima, Ceratoneis arcus var. hattoriana, C. a. var. vaucheriae, Cocconeis placentula, C. p. var. lineata, Cyclotella meneghiniana, Cymbella turgidula, C. uentricosa, C. v. var. girodi, Gomphonema angustatum var. producta, G. parvulum var. subelliptica, Navicula cinctaeformis, N. cryptocephala var. intermedia, N. viridula f. capitata, Nitzschia acicularis, N. dissipata, N. dubia var. australis, N. filiformis, Synedra rumpens, S. r. var. familiaris are newly recorded from East Ongul Island. departmental bulletin paper